Unravelling The Genetic Factors in The Pathogenesis of Amyotrophic Lateral Sclerosis (ALS) - -, Muthmainah (Cermin Dunia Kedokteran, 2017)
Progressive degeneration of the large motor neurons in the brain and spinal cord is a common finding in Amyotrophic Lateral Sclerosis (ALS). Several factors considered to underlie the disease have been proposed including genetic and environmental factor. Genetic factor have been well known to be highly implicated in the pathogenesis of ALS. Today, more than 20 genes contribute to the development of ALS. The pathologic hallmark of ALS is the accumulation of ubiquitinated protein aggregates. TDP-43 (TAR DNA binding protein, 43 kD) encoded by TARDBP gene was found to be the major component of these aggregates in most patients. Disruption of RNA binding capacity of TDP-43, either in the presence or absence of mutations will lead to the dysregulation of its targeted RNAs. Misregulation of RNAs regulated by TDP-43 is possibly a major cause of the disease.Degenerasi progresif dari neuron motorik di otak dan sumsum tulang adalah karakteristik dari penyakit ALS. Beberapa factor yang dianggap menjadi penyebab ALS antara lain adalah factor genetic dan factor lingkungan. Factor genetik diketahui berperan penting dalam pathogenesis ALS. Saat ini, lebih dari 20 gen telah teridentifikasi dan terlibat dalam perkembangan penyakit ini. Penanda patologis kelainan ini adalah adanya agregrat proteinyang tersebar. Komponen utama dari agregat ini adalah protein TDP-43 yang diatur oleh gen TARDBP-43. Gangguan dalam kemampuan mengikat protein dari TDP-43 akan menyebabkan kelaianan regulasi RNA yang menjadi target TDP-43. Gangguan regulasi RNA-RNA yang terikat pada protein ini diperkirakan menjadi penyebab utama penyakit ini.